Impact of long-term use of eHealth systems in adolescents with type 1 diabetes treated with sensor-augmented pump therapy. (July 2016) - Schiaffini, R; Tagliente, I; Carducci, C; Ullmann, N; Ciampalini, P; Lorubbio, A; Cappa, M
Telemedicine in diabetes includes telemonitoring and transmission of important data (self monitoring of blood glucose data, insulin therapy, pump setting, etc.) from the patient s home to the diabetic unit, with a real-time health feedback. Moreover, an eHealth approach is thought to facilitate diabetes management and to improve compliance to CSII/SAP treatment in adolescents, but to date, limited literature related to this topic is available and long-term studies are still lacking. The main aim of this study was to compare the long-term effect on glycometabolic control of eHealth intervention and traditional care in T1DM SAP-treated adolescents. In our study we demonstrated a favorable impact of monthly teleassistance on treatment compliance. Adolescents receiving frequent feedback provided by the medicalmultidisciplinary team, due to the telemonitoring, resulted more compliant in self-management of diabetes. In particular, the medical team feedback resulted in interventions on behavioral errors and insulin therapy adjustments, leading to an improved glycometabolic control.